’Borrego’, a new variety of xoconostle with nutritional and functional value for the Central Mesa region of Mexico - Gallegos-Vazquez, Clemente; Martínez-González, César Ramiro; Hernández-Fuentes, Alma Delia; García Mateos, Ma. del Rosario; Gallegos-Luevano, Nicolás Alejandro (Revista Mexicana de Ciencias Agrícolas, 2018)
From a cultural point of view, the xoconostles (Opuntia spp.) Have been an important factor in the economic sustenance of the peasant of the semi-arid zones of Mexico; however, to date, although xoconostles are a plant genetic resource with great potential, there are few works that allow us to know their diversity or their very existence. The recent efforts of the integrated inter-institutional group within the framework of the Nopal Network of the National System of Plant Genetic Resources for Food and Agriculture (SINAREFI), have allowed the rescue and evaluation of an important part of the diversity of xoconostles existing in Mexico. A new horticultural form of the genus Opuntia Miller (Cactaceae), considered as a variety of common use, is found in Villa of Tezontepec Municipality, Hidalgo, Mexico, known as xoconostle ‛Borrego’ (Opuntia oligacantha Förster). It was evaluated from 2012 to 2015 and it was found that its fruit is of medium size (74 ±1.09 cm) and oboval shape, with floral scar strongly sunken and very long peduncle (15.4 ±0.217 cm), with an external coloration of irregular coloration medium red, walls of pink hue, wide (10.6 ±0.363 mm, characteristic of the xoconostles), acidic (pH 3.22 ±0.039, dry to semi-dry and tasteless pink fungus, firm consistency, low sugar content (6.9 ±0.169 °Brix) and with an average number of fully developed seeds (218 ±1.723). The average yield in four years of evaluation was 13.59 t ha-1 and its fruits remain for more than six months in the plant, after the beginning of the This variety has the definitive registration Number XOC-026-290212 of the CNVV-SNICS and has been validated under the conditions of the central table of Mexico, in order to increase the varietal pattern for the commercial production of cactus in the region.